Digital Comics: Integrating CALL in Enhancing Students' Reading Skill at the High School Level - Sanjaya, Pandu Prima; Aminatun, Dyah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Computer-Assisted Language Learning (CALL) is a learning method that uses computer technology in the language learning process. This includes the use of software, applications, and other digital resources to assist students in learning English. Digital comics are a form of comic presented in digital format, which can be accessed and read via electronic devices such as computers, tablets or smartphones. This research aims to assess the effectiveness of learning CALL with digital comics in improving English reading skills. This research involves a pre-test and post-test comparison between experimental and control groups using narrative text material. There were 60 students from class XI. A and XI. C SMA 2 Muhammadiyah Bandar Lampung in the academic year 2023/2024. The results showed a significant increase in the scores of the experimental group post-intervention, especially in the higher score range (84-100). The findings show that the CALL method with digital comics is an effective tool to improve English reading skill among high school students.